ANALISIS SPASIAL PENGGUNAAN LAHAN KAMPUS UNIVERSITAS NEGERI PADANG MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) - Maiyenti, Elisa; Muhammad F. Octamal (Department of Civil Engineering, Faculty of Engineering, Universitas Negeri Padang, 2025)
This study aims to analyze and map land use distribution within the Air Tawar Campus of Universitas Negeri Padang (UNP) using Geographic Information Systems (GIS). Effective campus spatial management requires accurate and up-to-date spatial information to support academic activities and future development planning. The data used in this study include satellite imagery, campus boundary maps, and official supporting data such as building and facility records, land data, and road and bridge records as of December 31, 2022. The research methodology consists of data collection, georeferencing, land use digitization, field verification (ground check), and spatial analysis of land use area and proportions using QGIS software. The results indicate that built-up areas dominate the campus land use, covering approximately 60% of the total area, followed by open spaces and green open spaces at 31%, road networks at 7%, and river bodies at 2%. These findings highlight the importance of balanced land use planning to ensure sustainable campus development while maintaining environmental quality.